Cross-Validation of the Iowa Offender Risk Assessment Model in Michigan, 1980-1982 - Bradshaw, Richard Alfred ([Verlag nicht ermittelbar], 1989)
These data were collected in an attempt to cross-validate the 1984 and 1985 versions of the Iowa model for assessing risk of offending while on parole by applying the model to a Michigan sample of male parolees over a follow-up period of two and one-half years. Different measures of predictors such as prior criminal history, current offense, substance abuse history, age, and recidivism on parole are available. The first file contains information on parolees such as demographic characteristics, drug use history, prior criminal history, risk scores, and parole history. The second file includes parolees' detailed criminal histories including the total number of violent and nonviolent felony arrests and dates, and charges and dispositions of each arrest with a maximum of eight arrests.